Perencanaan Sistem Informasi di PERUMDAM TIRTA GALUH CIAMIS Menggunakan Metode Anita Cassidy - Naufal Hilmi At-Thorif; Rian Dwicahya Supriatman; Haisyam Maulana (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2026)
PERUMDAM Tirta Galuh Ciamis, as a clean water service provider, faces operational efficiency challenges, including manual customer data management, lack of system integration, and slow response to customer complaints. This study aims to develop a strategic information system (IS) plan aligned with PERUMDAM Tirta Galuh business objectives using the Anita Cassidy method, which consists of four stages: Visioning, Analysis, Direction, and Recommendation. The analysis was conducted using the Anita Cassidy method, which consists of four stages: Visioning, Analysis, Direction, and Recommendation. Value Chain approach to map business activities, Five Forces to assess competitiveness, and SWOT to identify strengths, weaknesses, opportunities, and threats. The research findings indicate that PERUMDAM requires digital-based information system enhancements, such as the development of a customer mobile application, integration of billing systems with GIS, as well as improvements in IT infrastructure and data security. The strategic recommendations include four priority projects: (1) Integrated Customer Management Information System, (2) Mobile Application for Payments and Complaints, (3) SCADA/IoT for Water Network Monitoring, and (4) IT Human Resource Training.